2013
DOI: 10.1007/s12262-012-0802-3
|View full text |Cite
|
Sign up to set email alerts
|

Impalement Injury with Transanal Prolapse of Bowel Content Due to Intraperitoneal Rectal Tear

Abstract: A 48-eight-year-old female patient came with prolapse of small intestines per rectum ( Fig. 1) due to impalement injury with iron rod at a construction site. As the patient was hemodynamically unstable, she was taken for emergency laparotomy. A large rent in the intraperitoneal rectum was found (Fig. 2), with prolapse of intestines. Luckily for the patient, there was no other intra-abdominal organ injury. As there was no fecal contamination at all, a decision against proximal colostomy was made. The rent was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Eight case reports involving nine patients with steel rod impalement injuries involving the spine were identified in an extensive review of the English literature on PubMed (Table 1). We concluded that steel rod impalement injuries sparing the spine are not extremely rare, with different entrance sites, such as the oral cavity, [2] orbita, [3] nose, [4] cranium, [5] neck, [6] thorax, [7] abdomen, [8] hand, [9] rectum, [10] buttock, [11] and groin. [12] Most victims of steel rod impalement injuries are construction workers, and we believe that occupational safety specialists have to focus on this type of injury to decrease the incidence of this mostly preventable condition.…”
Section: Discussionmentioning
confidence: 92%
“…Eight case reports involving nine patients with steel rod impalement injuries involving the spine were identified in an extensive review of the English literature on PubMed (Table 1). We concluded that steel rod impalement injuries sparing the spine are not extremely rare, with different entrance sites, such as the oral cavity, [2] orbita, [3] nose, [4] cranium, [5] neck, [6] thorax, [7] abdomen, [8] hand, [9] rectum, [10] buttock, [11] and groin. [12] Most victims of steel rod impalement injuries are construction workers, and we believe that occupational safety specialists have to focus on this type of injury to decrease the incidence of this mostly preventable condition.…”
Section: Discussionmentioning
confidence: 92%
“…Impalement is defined as injuries caused by foreign bodies, usually steel bars, or wooden objects, which pierce body cavities or extremities and remain interposed in the perforated body region [ 1 ]. This type of trauma corresponds to an injury spectrum occasionally reported in the literature, being more frequent in the thoracic, abdominal and perineal areas [ 2 , 3 , 4 ]. Its report at the extremity level is even rarer [ 5 ].…”
Section: Introductionmentioning
confidence: 85%